1999
DOI: 10.1111/j.1468-3083.1999.tb00841.x
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary vulva clinic: the role of genito‐urinary medicine

Abstract: Despite having genitourinary symptoms less than half the patients had been tested for infection prior to attending the clinic. More than a third of the patients, 46 (34%), were diagnosed with a genitourinary infection. There is a significant role for genitourinary services in the diagnosis, management and ongoing care of patients in a vulva clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
(14 reference statements)
0
17
2
Order By: Relevance
“…Lichen planus (LP) is a chronic inflammatory dermatosis that affects skin, mucous membranes, and nails . A multidisciplinary vulvar clinic study highlighted a prevalence of 3.7% for biopsy‐proven vulvar LP (VLP) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichen planus (LP) is a chronic inflammatory dermatosis that affects skin, mucous membranes, and nails . A multidisciplinary vulvar clinic study highlighted a prevalence of 3.7% for biopsy‐proven vulvar LP (VLP) .…”
Section: Discussionmentioning
confidence: 99%
“…Sullivan et al . found that the majority (87%) of the patients had chronic vulval conditions with symptom duration greater than 6 months before diagnosis (range 1 to >10 years).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and prevalence figures have not been established, but the present author would estimate that it occurs in about 0.5% of the Western European and American population. In clinics devoted solely to the care of patients with vulvar disorders, LSC accounts for 10–35% of the patients seen (1–3). It develops predominantly in mid‐ to late adult life, but it certainly also occurs in children.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of the most effective management options for GH may require the pooling of physician resources. In Sweden, for example, specialists in gynaecology and dermatovenereology work together to optimize female patient care at so‐called ‘vulval clinics’ 8 . In France, STD specialists, gynaecologists and dermatologists work together in some STD clinics.…”
Section: Today's Management Of Recurrent Genital Herpes: Primary and mentioning
confidence: 99%